Environmental Law Enforcement on Illegal Rock Mining in Indonesia: A Case Study of Bone Regency - Saputri, Lestary (IAIN Bone, 2024)
Rock mining plays an important role in meeting infrastructure needs, yet it is often conducted without official government authorization, posing serious environmental and economic risks. This study aims to evaluate the effectiveness of environmental law enforcement on illegal rock mining activities in Bone Regency, Indonesia. Using a normative juridical approach complemented by field research, data were collected through observations, interviews, and official documentation. The findings indicate that although Law No. 3 of 2020 on Mineral and Coal Mining prescribes sanctions for violators, its enforcement has not yet created a sufficient deterrent effect. Key challenges include weak regulatory frameworks, the absence of specific local regulations on mining zones, and low community awareness, which continue to drive illegal mining practices. This study recommends stricter law enforcement measures, development of region-specific regulations, public education on the negative impacts of illegal mining, and shifts in community mindset toward sustainable mining practices. A comprehensive approach is essential for achieving effective and sustainable environmental law enforcement and minimizing the negative impacts of illegal mining on the environment and local communities